2018
DOI: 10.1037/cap0000136
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation, plans, and attempts among public safety personnel in Canada.

Abstract: This is a temporary placeholder file. An open access version will be added if it becomes available. Pease click on the DOI link to access the publisher version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
144
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(167 citation statements)
references
References 72 publications
20
144
2
1
Order By: Relevance
“…Data were drawn from an open Web-based survey (Qualtrics, https://www.qualtrics.com/) of Canadian public safety personnel available online from Sept. 1, 2016, to Jan. 31, 2017. 2,5 Survey participation was self-selected and voluntary, which made this a convenience sample. The survey modules were developed by the Canadian Institute for Public Safety Research and Treatment Team, which included the Canadian Association of Chiefs of Police, the Canadian Association of Fire Chiefs, the Canadian Association of Police Governance, the Canadian Police Association, the Correctional Service of Canada, the International Association of Fire Fighters, the Paramedic Association of Canada, the Paramedic Chiefs of Canada, the Royal Canadian Mounted Police and the Union of Solicitor General Employees, as well as the University of Regina, where one of the authors (R.N.C.)…”
Section: Data and Samplementioning
confidence: 99%
“…Data were drawn from an open Web-based survey (Qualtrics, https://www.qualtrics.com/) of Canadian public safety personnel available online from Sept. 1, 2016, to Jan. 31, 2017. 2,5 Survey participation was self-selected and voluntary, which made this a convenience sample. The survey modules were developed by the Canadian Institute for Public Safety Research and Treatment Team, which included the Canadian Association of Chiefs of Police, the Canadian Association of Fire Chiefs, the Canadian Association of Police Governance, the Canadian Police Association, the Correctional Service of Canada, the International Association of Fire Fighters, the Paramedic Association of Canada, the Paramedic Chiefs of Canada, the Royal Canadian Mounted Police and the Union of Solicitor General Employees, as well as the University of Regina, where one of the authors (R.N.C.)…”
Section: Data and Samplementioning
confidence: 99%
“…Third, the reliability and validity of web-based selfreports remains ambiguous 41 ; nevertheless, the high frequencies and relatively large sample appear to justify research with more robust assessments (e.g., interviews; random sampling). Fourth, the PSP category groupings were based on previous research 29,42,43 but could not account for potentially important differences within some categories (e.g., paramedics verses emergency medical technicians). Fifth, future research should simultaneously assess the interactive effects of mental health and chronic pain, given the substantial evidence of comorbidity [44][45][46][47] and potentially increased risk from mutually maintaining factors.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, an Australian study reported a higher prevalence of mental illness among the police and emergency services than other professions (Harman 2019). Likewise, in Canada, mental illness is widespread among police officers; high proportions of them reported having suicidal ideation (10% during the past year, 28% in lifetime), planned suicide (4% during the past year, 13% in lifetime), and attempted suicide (0.4% during the past year, 5% in lifetime) (Carleton et al 2018; The Centre for Addiction and Mental Health (CAMH) 2018). Mental wellbeing of police officers is a cause for concern in many countries, highlighting the need for further study.…”
mentioning
confidence: 99%